A call for a wider perspective on sustainable forestry: Introduction to the Special Issue on The Social Impacts of Logging - Minter, T.; Naito, D.; Sunderland, T.C.H. (Commonwealth Forestry Association, 2023)
Global demand for timber is projected to grow and much of this timber will continue to be sourced from natural forests. As these forests, particularly in the tropics, tend to be inhabited by the world's most marginalized communities, the social impacts of logging require more attention within policy, practice and research. This Introduction to the Special Issue of International Forestry Review on The Social Impacts of Logging compiles evidence that the overwhelmingly negative social impacts of logging are systemic. As logging companies fail to fulfill their social obligations, and elite capture is common, the extent to which local communities benefit from logging operations is minimal, while long-term, harmful effects on livelihoods, social fabric and safety are severe. Logging operations reinforce and often exacerbate pre-existing inequities, particularly for women and Indigenous people. Weak governance, a lack of transparency and poor participation procedures partially explain this unfavourable situation. However, logging will only achieve better social outcomes if underlying power-imbalances are tackled.